Derivation of Equations for Flexure and Shear Deflections of Simply Supported Beams - Ümran ESENDEMİR (Pamukkale University Journal of Engineering Sciences, 2009)
Shear deflection of wood beams generally is exluded in plannning calculations. Ignoring shear deflection could cause significant errors, expecially for short and thick beams. In this study, two deflection functions due to flexure and shear of simply supported composite beam subjected to single force are obtained analytically. Wood being high shear modulus according to other material is selected for sample problem. The deflections the mid point of the beam are calculated to see the effect of shear by using the obtained functions for 0, 15, 30, 45, 60 and 90 orientation angles. Also, bending stresses at the mid point of the short beam are given for 0, 15, 30, 45, 60 and 90 orientation angles. It is shown that the magnitude of shear deflection depends on force, length and height of the beam. The shear effect is the smallest for 45 orientation angle and the biggest for 0 orientation angle.